Aberrant Forms of Streptococcus cremoris HP - Keogh, Barbara P. (1981)
The cheese starter strain, Streptococcus cremoris HP, produced variant colonies when streaked on the surface of solid media and incubated at 30 or 37°C or in the presence of penicillin. Serial plating and incubation at 37°C or in the presence of penicillin resulted in the production of variants. Subculture followed by incubation at 25°C or in the absence of penicillin resulted in the reversion or partial reversion to the parent form. Colony morphology and cell morphology exhibited the characteristics of the L-phase. Evidence suggested that the aberrant forms of S. cremoris at 30°C were transitional phase variants but at 37°C and in the presence of penicillin they were L-phase variants. Electron micrographs showed that the cell walls of the variant cells were defective and that there were differences in the density and the organization of the cytoplasmic constituents compared with the parent cell.